Behavioural drivers of fertility in red junglefowl Gallus gallus and commercial chicken flocks - Pasternack Murray, EO (2022)
The fowl, Gallus gallus, has been used to study sexual behaviour and sexual selection for many years: its combination of reproductive biology that is fairly typical of birds and a polygynandrous mating system makes it an ideal model species for studying the effects of pre- and post- copulatory competition and of conflict between the sexes. There is a large body of research spanning many decades on these processes in domestic chickens and their wild ancestor, the red junglefowl. As well as being an ideal model system, the sexual behaviour and fertility of this species is of great significance to the poultry industry, where the reproductive efficiency of broiler breeders (birds whose commercial purpose is to produce hatching eggs) is a key concern. However, the behaviour of broiler breeders in a commercial setting, and how their behaviour links to fertility, is little understood.